Analysis Of Factors Affecting Job Participation and Income Of Female Migrant Workers In Denpasar City - Dela Anisa Putri; Ida Ayu Nyoman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Migration is one of the three components of population growth besides births and deaths. The large number of migrants in Bali Province, especially Denpasar City, indicates that the decision to migrate is quite high. Looking at the composition of the female migrant population, which dominates, this shows that the number of women migrating to Denpasar City is higher than the male population. This research aims to analyze the direct and indirect influence of education level, number of dependents and husband's employment status on the amount of working hours and income of female migrant workers. The number of samples used in this research was 100 samples. The analysis techniques used are descriptive analysis techniques and path analysis. The results of this study show that the level of education and number of family dependents have a positive effect on the amount of working hours, work experience does not have a negative effect on the amount of working hours, female migrant workers with the employment status of working husbands devote fewer working hours compared to respondents whose husbands do not work. , level of education, work experience and number of family dependents have a positive effect on income, female migrant workers with employment status and working husbands earn lower income than respondents whose husbands do not work, the number of hours worked has a positive effect on income, the number of hours worked mediates the effect education level, work experience, number of family dependents and husband's employment status on the income of female migrant workers.